1998
DOI: 10.1111/0022-1082.194060
|View full text |Cite
|
Sign up to set email alerts
|

Option Volume and Stock Prices: Evidence on Where Informed Traders Trade

Abstract: This paper investigates the informational role of transactions volume in options markets. We develop an asymmetric information model in which informed traders may trade in option or equity markets. We show conditions under which informed traders trade options, and we investigate the implications of this for the linkage between markets. Our model predicts an important informational role for the volume of particular types of option trades. We empirically test our model's hypotheses with intraday option data. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

73
774
5
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 987 publications
(853 citation statements)
references
References 47 publications
73
774
5
1
Order By: Relevance
“…Apart from reducing information asymmetry, Black (1975) notes that informed traders could use options markets as an alternative venue for trading because option contracts provide higher leverage. Easley, O'Hara, and Srinivas (1998) argue that options can be more attractive for informed traders because the availability of multiple contracts confronts uninformed traders with substantial challenges. In a similar vein, Cao (1999) suggests that agents with private information should be able to trade more effectively on their information in the presence of options, thus improving price informativeness.…”
Section: Related Literaturementioning
confidence: 99%
“…Apart from reducing information asymmetry, Black (1975) notes that informed traders could use options markets as an alternative venue for trading because option contracts provide higher leverage. Easley, O'Hara, and Srinivas (1998) argue that options can be more attractive for informed traders because the availability of multiple contracts confronts uninformed traders with substantial challenges. In a similar vein, Cao (1999) suggests that agents with private information should be able to trade more effectively on their information in the presence of options, thus improving price informativeness.…”
Section: Related Literaturementioning
confidence: 99%
“…We find firstly that the previous finding (Black, 1975;Easley et al, 1998) that informed traders prefer options to stocks and are willing to make profits by trading options instead of stocks, still holds in the S&P 500 index option market. Secondly, volatility curvatures extracted from the implied volatility functions and skewness premiums extracted from the risk-neutral probability density respectively are found to possess valuable information on the market direction, which sup-1) Although there is a distinction between long term and short term trading for a corporate trader, we set '60/40' principle for individual trader.…”
Section: Resultsmentioning
confidence: 50%
“…Black (1975) and Easley, O'Hara and Srinivas (1998) argue that an informed trader would prefer to trade options to stocks because of options' leverage effect. Manaster and Rendleman (1982), Bhattacharya (1987), Amin and Lee (1997), Chan, Chung, and Fong (2002), Cao, Chen and Griffin (2005) and Pan and Poteshman (2006) find that some informed trades on options achieve excess rates of return and that option market quotes contain information about future stock returns.…”
Section: Introductionmentioning
confidence: 99%
“…After Anthony 1 showed the interrelation of stock and option market trading-volume, Easley et al 2 rejected the hypothesis that option volume contains no information about future spot prices. In their empirical study, the latter authors show that past option volumes have information content.…”
Section: The Literaturementioning
confidence: 99%
“…Thus, Equation (2) does not add much to Equation (1) and is estimated in accordance with previous studies. Since Easley et al 2 found a significant effect of the total volume of trade (puts and calls together) on the price of stocks, it was chosen as an explanatory variable in Equation (2). An econometric analysis performed by Simon and Wiggins 9 tried to examine the predictive power of PCR together with other sentiment indicators.…”
Section: The Modelmentioning
confidence: 99%